ANALISIS PENGARUH LOKASI, PERSEPSI HARGA DAN KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN TOKO SARI KALIGAWE, SEMARANG (studi pada Toko Sari Kaligawe, Semarang) - Adhimas Putra, Samuel; Darmastuti, Ismi (Diponegoro Journal of Management, 2013)
This research was triggered by theincreasment of competitionin the grocery retail business which is characterized by the emergence of many minimarket’s in recent years. Sari store’s customers have been decreased in just past four months, from January to April 2013. Besides, Sari store has several new competitors like Indomaret, Alfamart, etc. Effort to maintain customer loyalty is toimprove service quality. The aim of this research is to analyze the influence of location, price perception and service quality towards customers loyalty in Sari store.The questionnaire data are collected from 75 respondents. Validation test, reliability test, classic assumption test (Normality test, Multicolinearity test, heteroskedasticity test), multiple linear regression analysis, and goodness of fit test (F test, t test, determination coefficient) will be used to analyze.From regression analysis, we know that location, price perseption, and service quality variable have the positive effect for customer’s loyalty at Sari store. The service quality variable is the most influential for customer’s loyalty. All of the three variable have 54.1% of customer’s loyalty, and the rest percentage is affected by the others variables.The results of this research indicate that the location have positive impact on customers loyalty. price perception impacting positively on customers loyalty. service quality have positive impact on customers loyalty.